Evidence according to Cochrane Systematic Reviews on Alterable Risk Factors for Anastomotic Leakage in Colorectal Surgery - Bradley Wallace; Fabia Schuepbach; Stefan Gaukel; Ahmed I. Marwan; Ralph F. Staerkle; Raphael N. Vuille-dit-Bille (Gastroenterology Research and Practice)
Anastomotic leakage reflects a major problem in visceral surgery, leading to increased morbidity, mortality, and costs. This review is aimed at evaluating and summarizing risk factors for colorectal anastomotic leakage. A generalized discussion first introduces risk factors beginning with nonalterable factors. Focus is then brought to alterable impact factors on colorectal anastomoses, utilizing Cochrane systematic reviews assessed via systemic literature search of the Cochrane Central Register of Controlled Trials and Medline until May 2019. Seventeen meta-anaylses covering 20 factors were identified. Thereof, 7 factors were preoperative, 10 intraoperative, and 3 postoperative. Three factors significantly reduced the incidence of anastomotic leaks: high (versus low) surgeon’s operative volume (RR=0.68), stapled (versus handsewn) ileocolic anastomosis (RR=0.41), and a diverting ostomy in anterior resection for rectal carcinoma (RR=0.32). Discussion of all alterable factors is made in the setting of the pre-, intra-, and postoperative influencers, with the only significant preoperative risk modifier being a high colorectal volume surgeon and the only significant intraoperative factors being utilizing staples in ileocolic anastomoses and a diverting ostomy in rectal anastomoses. There were no measured postoperative alterable factors affecting anastomotic integrity.